2010
DOI: 10.4314/njps.v23i1-2.54915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on testicular functions in male sprague-dawley rats

Abstract: Summary:Variation in reproductive status in response to photoperiods has been observed in laboratory rats. We investigated the effects of photoperiod on testicular activity in Sprague-Dawley rats (Rattus norvigicus) maintained in experimental photoperiodic condition. Twenty four adult male rats weighing 170±10g were conditioned to different lighting conditions of Light/Dark (LD) Cycle for 6 weeks. Group 1, Control group (LD12:12, light on from 07:00hr to 19:00hr). Group 2, Short Photoperiod group (LD 8:16hr, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Serum testosterone, testicular weight, diameter of seminiferous tubules, Leydig cell mitochondria and cytoplasmic secretory granules, sperm motility, viability and count are increased by long photoperiods [12,54,55]. All of these parameters decline with aging [56,57] along with the levels of TRH and TRH-like peptides in brain and peripheral tissues [3].…”
Section: Discussionmentioning
confidence: 99%
“…Serum testosterone, testicular weight, diameter of seminiferous tubules, Leydig cell mitochondria and cytoplasmic secretory granules, sperm motility, viability and count are increased by long photoperiods [12,54,55]. All of these parameters decline with aging [56,57] along with the levels of TRH and TRH-like peptides in brain and peripheral tissues [3].…”
Section: Discussionmentioning
confidence: 99%
“…Some diurnal rodents, such as fat sand rats (Psammomys obesus; males), Nile grass rats (Arvicanthis niloticus; males), and nocturnal rodents (Rattus norvegicus [Wistar rats]), presented numerous traits that were modulated by the specific photoperiod, including negative affective responses [12][13][14]. Sprague-Dawley rats are photoresponsive, and changes in the photoperiod can influence their reproductive functions [15]. However, whether mood states in Sprague-Dawley rats are photoresponsive has not been previously studied, and the role of a short photoperiod in the susceptibility to stress in adolescence is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ben Saad and Maurel (2002) reported that short photoperiod has an improvement effect on male reproductive characteristics in wild rabbits. Moreover, long photoperiod resulted in non-significant increase in sperm properties, but it increased the testis weight (Olayaki et al 2008). This result disagree with Petrocelli et al (2015), who showed that long photoperiod has significantly effect on the sperm concentration.…”
Section: Discussionmentioning
confidence: 66%